Forage Yield and Quality of Different Genotypes o-f-Buffel Grass (Cenchrus ciliaris Linn.) at Various Cutting Intervals - Patidar, M; Rajora, M P (Annals of Arid Zone, 2016)
A field experiment was conducted at Jodhpur during kharif season from 2004 to 2006 under rain fed conditions to study the performance of four Cenchr s ciliaris genotypes (CAZRI 2171, CAZRI 2186, CAZRI 2226 and CAZRI 75) with hree cutting sclledules, i.e. 30, 45 and 60 days intervals for forage yield and quality. The results of;three yea s revealed that maximum mean dry matter (1990 kg ha-1 ) and protein yield (20’i’kg ha-1 )Iwere with CAZRI 2171 followed by CAZRI 2226, whereasCAZRI 75 had minimum dry ratter (846 kg ha-1) and protein yield (64 kg ha-1 ). Plants of CAZRI 2171 and 222:6were taller and flowered early while number of tillers were mOre with CAZR 2186. Protein c ntent was slightly higher in the foliage of CAZRI 75, but total protein yield was lower t an CAZRI 2171 and CAZ 2226. This indicated that CAZRI,2171 and CAZRL2226 we e superior for producing higher quality fodder under arid conditions. Cutting intervals di not show significant variation for dry matter production over the years, but green fodde yield and crude protein content were higher with 30 days interval iI1 all the genotype . Key words: Buffel grass, Cenchrus ciliaris, genotype, cutting intervals.â€¢